KEDUDUKAN HUKUM SKGR SEBAGAI JAMINAN HUTANG PIUTANG DALAM PERSPEKTIF AGRARIA DAN PERDATA - Vallgyvan Saptuma Effendi, (Proceeding International Conference on Social Sciences, 2026)
The Statement of Compensation Letter (Surat Keterangan Ganti Rugi or SKGR) serves as proof of land possession and is usually issued by a village head or subdistrict head, particularly in areas not yet reached by the National Land Agency’s (BPN) land certification program. In practice, SKGR is often used as collateral in loan agreements, raising legal concerns because it is not recognized as valid evidence of land ownership under the Basic Agrarian Law No. 5 of 1960 and its implementing regulations. This study aims to examine the legal status of SKGR when used as collateral, analyze its implications for the protection of landowners’ rights, and review the judicial considerations in Decision No. 254/PDT.G/2021/PN Pekanbaru. The research applies a normative-empirical juridical approach, combining statutory analysis, legal doctrines, and court decision studies. The results show that SKGR functions merely as proof of land possession and cannot be considered conclusive evidence of ownership. Its use as collateral therefore carries substantial legal risk. Legal protection for SKGR holders remains weak due to the absence of clear regulations defining its position within Indonesia’s agrarian law system. The court’s reasoning in Decision No. 254/PDT.G/2021/PN Pekanbaru also affirms that SKGR does not have equal legal standing with land certificates and thus fails to ensure legal certainty in loan transactions. This study concludes that specific regulation is required to strengthen the legal status of SKGR and to guarantee legal certainty and balanced protection for both landowners and creditors.